Honeypot Visualization Mapping System (HVMS) / Mohamed Syafiq Khan Mohamed Seth - Mohamed Seth, Mohamed Syafiq Khan (2012)
Honeypot visualization mapping System (HVMS) is a security tool to represent data via google map. This project is created to counter honeypot logfile that are difficult to read and time consuming. The visualization tool will also help communicate results and get better understanding of a situation in a quicker manner. This will help people to make decision faster especially when the honeypot is being attacked. In building this project, a lot of research will be made by gathering related information through consulting experts and finding method through Internet. This project is developed in a CakePHP framework. The objective of this project is to develop a visualization system that can read the honeypot log file, display the location of the ip address and can provide direction to the location of the IP address in a map. By using this project, users will be able to identify the attacker location. When an attack is detected, the system will retrieve the IP address in the honeypot logfile to be compared to the IP address in Ipinfodb database. As a result, the location of the attacker will be retrieve from the Ipinfodb database by using Xml Api. Finally, the location will be display on google map using google map API (an application programming interface use to build google map). It is hope that the result of this project will give benefits to all users and to the network admin in taking action faster by detecting the attacker location quicker.